[tex]✏ Answer:[/tex]
••••••••••••••••••••••••••••••••••••••••••••••••••
Product of the First terms (F)
3.) (x) (x) = x²
4.) (2x) (x) = 2x²
••••••••••••••••••••••••••••••••••••••••••••••••••
Product of the Outer terms (O)
3.) (x) (-3) = -3X
4.) (2x) (2) = 4x
••••••••••••••••••••••••••••••••••••••••••••••••••
Product of the Inner terms (I)
3.) (2) (x) = 2x
4.) (5) (x)= 5x
••••••••••••••••••••••••••••••••••••••••••••••••••
Product of the Linner terms (L)
3.) (2)(-3) = -6
4.) (5) (2) = 10
••••••••••••••••••••••••••••••••••••••••••••••••••
Sum of outer and inner terms O+I
3.) (-3x) + 2x = -x
4.) 4x+5x = 9x
•••••••••••••••••••••••••••••••••••••••••••••••••
F+ (0+1)+L
3.) x²-x-6
4.) 2x² + 9x + 10